Preparation method of water-based silicon dioxide core-shell structure coating liquid photovoltaic glass

By using aqueous silica core-shell structure coating solution on photovoltaic glass, a coating with excellent anti-reflection, wear resistance and self-cleaning performance is formed, which solves the problems of light reflection loss, surface wear and pollutant accumulation during long-term use of photovoltaic glass, and achieves a significant improvement in the performance and service life of the photovoltaic system, and is environmentally friendly and low-pollution.

CN119912174APending Publication Date: 2025-05-02FLAT GLASS GROUP CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411985751.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Photovoltaic glass faces problems such as photoreflection loss, surface wear, and accumulation of pollutants during long-term use, resulting in reduced photoelectric conversion efficiency and shortened service life. The existing coating technology has defects such as poor durability and insufficient environmental protection.

Method used

The aqueous silica core-shell structure coating solution is used to prepare the coating solution by the sol-gel method, and organic silane and fluoride are added to form a core-shell structure coating, which improves anti-reflection, wear resistance and self-cleaning properties, and enhances the adhesion and stability of the coating through medium-temperature annealing treatment.

Benefits of technology

Significantly improve the performance and durability of photovoltaic systems, improve light transmittance by 3 to 5%, extend service life by 3 to 5 times, and at the same time, it has the characteristics of environmental protection and low pollution, and meets the requirements of green manufacturing.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a preparation method of water-based silicon dioxide core-shell structure coating liquid photovoltaic glass, and belongs to the technical field of photovoltaic glass, the preparation method comprises the following steps: S1, preparing raw materials of silicon dioxide, organosilane, fluoride and a water-based solvent; s2, preparing a coating solution, namely preparing a water-based silicon dioxide core-shell structure coating solution by a sol-gel method, adding silicon dioxide nanoparticles into deionized water, and dispersing to obtain silicon dioxide sol; adding a proper amount of organosilane and fluoride into the silicon dioxide sol, and uniformly mixing to form a core-shell structure; adjusting the pH value of the solution according to formula requirements; continuously stirring for a certain time to form a stable water-based dispersion liquid; s3, coating and drying are performed according to the surface morphology of the photovoltaic glass by selecting a dip-coating method, spray coating or spin coating; and drying treatment: putting the coated photovoltaic glass substrate into a drying oven, carrying out primary drying, and then carrying out medium-temperature annealing treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photovoltaic glass, and in particular to a method for preparing photovoltaic glass with an aqueous silicon dioxide core-shell structure coating liquid. Background Art

[0002] Photovoltaic technology, as an important clean energy solution, has been widely used. In photovoltaic power generation systems, photovoltaic glass, as an important component of photoelectric conversion components, directly affects the performance and service life of the entire system. However, photovoltaic glass faces some key problems during long-term use, such as light reflection loss, surface wear, and accumulation of pollutants. These problems not only reduce the conversion efficiency of the photovoltaic system, but also shorten the service life of photovoltaic glass.

[0003] Problems with existing technologies:

[0004] Light reflection loss problem: Due to the optical properties of the photovoltaic glass surface, light reflection will cause part of the light energy to be unable to effectively enter the photovoltaic cell, thus affecting the photoelectric conversion efficiency. In order to improve the light transmittance of photovoltaic glass and reduce reflection loss, many studies have focused on improving the anti-reflection performance of photovoltaic glass. Common technologies include adding anti-reflection coatings to the glass surface, but traditional coatings have defects such as poor durability and poor environmental protection.

[0005] Challenges of wear resistance and self-cleaning performance: The surface of photovoltaic glass is exposed to the outdoor environment and is easily eroded by natural factors such as wind, sand, and rain, resulting in surface scratches and dirt accumulation, affecting its long-term stability and performance. Especially in extreme environmental conditions such as sandstorms, the wear resistance and self-cleaning performance of photovoltaic glass are particularly important. Therefore, improving the wear resistance and self-cleaning ability of photovoltaic glass has become one of the key technologies to improve its long-term performance.

[0006] Environmental protection requirements: With increasingly stringent environmental regulations, traditional organic solvent-based coatings contain toxic chemicals, pose environmental pollution risks, and do not meet the requirements of green manufacturing. Therefore, the development of more environmentally friendly and low-pollution water-based coatings has become an important direction for the development of photovoltaic glass coating technology. Water-based coatings can not only reduce the negative impact on the environment, but also enhance the market competitiveness of products.

[0007] Limitations of existing technologies: Although existing technologies have made certain progress in the anti-reflection, wear resistance and self-cleaning functions of photovoltaic glass, most of the existing coating technologies have the following problems: the stability and adhesion of the coating are not strong, and it cannot maintain high efficiency in long-term use; some coatings are difficult to maintain self-cleaning effects under complex environmental conditions; in addition, many coating technologies also have problems such as insufficient environmental protection and high preparation costs.

[0008] Therefore, there is an urgent need for a new photovoltaic glass coating technology that can improve the photoelectric conversion efficiency while enhancing its wear resistance and self-cleaning ability, while also being environmentally friendly and sustainable. Summary of the invention

[0009] In order to overcome the above-mentioned defects of the prior art, the present invention provides a method for preparing photovoltaic glass with an aqueous silica core-shell structure coating liquid to solve the problems raised in the background technology.

[0010] In order to achieve the above-mentioned object of the invention, the present invention provides a method for preparing photovoltaic glass with an aqueous silica core-shell structure coating liquid, the preparation method comprising:

[0011] S1: Preparation of raw materials

[0012] Silicon dioxide, as the core material of the core-shell structure, has good optical properties and is suitable as a substrate for anti-reflective coatings;

[0013] Organosilane, used to coat the surface of silica particles to enhance the adhesion and water resistance of the coating;

[0014] Fluoride, as the outer layer of the coating, gives the coating good hydrophobicity and enhances its self-cleaning function;

[0015] Aqueous solvent, using deionized water as the aqueous solvent;

[0016] S2: Preparation of coating solution: Preparation of water-based silica core-shell coating solution by sol-gel method: Add silica nanoparticles into deionized water and disperse them to obtain silica sol;

[0017] Add appropriate amounts of organosilane and fluoride to the silica sol, and stir with a magnetic stirrer to make them evenly mixed. At this time, the organosilane and sodium fluoride will combine with the silica particles to form a core-shell structure;

[0018] According to the formula requirements, the pH value of the solution is adjusted to 5-6 to ensure that the hydrolysis and polycondensation reactions of the organosilane proceed smoothly;

[0019] Continue stirring for a certain period of time to ensure that all ingredients react completely to form a stable aqueous dispersion;

[0020] S3: Coating and Drying

[0021] Select dip coating, spray coating or spin coating for coating according to the surface morphology of photovoltaic glass;

[0022] Drying treatment: Place the coated photovoltaic glass substrate in an oven for preliminary drying, set the oven temperature, and control the drying time to ensure that the coating adheres stably to the glass surface; in order to further improve the adhesion and wear resistance of the coating, a medium-temperature annealing treatment is used. Place the photovoltaic glass substrate on a heating plate, set the temperature to 120°C, and anneal for 20 minutes to further fix the coating and improve the density and stability of the coating;

[0023] S4: Coating Optimization

[0024] The refractive index of the coating can be controlled by adjusting the particle size and distribution of silica particles, and the wear resistance and self-cleaning properties of the coating can be further improved by adjusting the ratio of organosilane and fluoride in the coating.

[0025] S5: Performance Evaluation and Testing

[0026] Including light transmittance test, abrasion resistance test and self-cleaning performance test.

[0027] Furthermore, the silicon dioxide is silicon dioxide nanoparticles with a particle size of 30 to 50 nm.

[0028] Furthermore, the organosilane is methyltriethoxysilane or MTES, and the fluoride is sodium fluoride.

[0029] Furthermore, in step S2, after adding the silica nanoparticles into deionized water, an ultrasonic oscillator is used to disperse the silica nanoparticles. The oscillation time is 30 to 40 minutes and the power is 500 W to obtain silica sol.

[0030] Furthermore, the hardness of the coating is greater than or equal to 3H, and the surface friction coefficient is less than 0.2.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] The aqueous silica core-shell structure coating liquid photovoltaic glass of this application can significantly improve the performance and durability of photovoltaic systems:

[0033] Anti-reflection performance: Improve the light transmittance of photovoltaic glass, increase the overall photoelectric conversion efficiency by 3-5%, and reduce light reflection loss;

[0034] Wear resistance: Enhance the wear resistance of the glass surface and extend the service life of photovoltaic glass by 3 to 5 times;

[0035] In addition, the coating itself uses water-based coating liquid, which is environmentally friendly and pollution-free, meets the requirements of green manufacturing, and has good market application prospects. Photovoltaic glass can maintain stable performance under various environmental conditions, providing a guarantee for the long-term and reliable operation of the photovoltaic system. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the invention, not all of the embodiments. The embodiments of the present invention are described below in conjunction with the accompanying drawings.

[0037] At present, the performance improvement and protection technology of photovoltaic glass are mainly concentrated in the following aspects:

[0038] 1. Anti-reflective coating technology:

[0039] The anti-reflective coating of photovoltaic glass is designed to increase light transmittance and reduce light reflection loss, thereby improving photoelectric conversion efficiency. Existing anti-reflective coatings mostly use metal oxides (such as TiO2, SiO2, etc.) or silicone coatings, which can reduce the reflectivity of the surface, thereby improving the transmittance of sunlight and the overall efficiency of the photovoltaic system. However, traditional coatings have certain deficiencies in wear resistance and self-cleaning functions. After long-term use, they are easily affected by environmental factors, resulting in coating damage, affecting the long-term performance of photovoltaic glass;

[0040] 2. Wear-resistant coating technology:

[0041] In order to improve the wear resistance of photovoltaic glass, there are some coating technologies on the market, mainly using hardened coatings or transparent protective films. These coatings can improve the scratch resistance of the glass surface to a certain extent, but they are easy to fall off or fail during long-term use, and cannot effectively extend the service life of photovoltaic glass;

[0042] 3. Self-cleaning coating technology:

[0043] Self-cleaning coating technology often uses coating materials with super-hydrophobicity or super-hydrophilicity to automatically remove dust and dirt from the glass surface by using the rolling effect of water. Existing self-cleaning coatings usually use materials such as silicon dioxide (SiO2) and fluoride to improve the self-cleaning ability of photovoltaic glass surfaces. However, the durability and stability of these coatings are still challenged, especially in harsh climates and long-term use conditions, the coatings may fail, resulting in a decrease in the self-cleaning effect;

[0044] 4. Environmentally friendly coating technology:

[0045] Traditional photovoltaic glass coating technology usually relies on solvent-based coating liquids. Such coating materials may release harmful solvents during use, which may cause certain environmental pollution problems. In recent years, environmentally friendly water-based coatings have gradually attracted attention because they have the advantages of low volatile organic compound (VOC) emissions, non-toxicity and pollution-free, and meet the requirements of green manufacturing. However, the existing water-based coating technology still has certain technical bottlenecks in the comprehensive performance of photovoltaic glass (such as anti-reflection, wear resistance, weather resistance, etc.);

[0046] Technical bottlenecks of existing technologies: Although existing technologies have achieved good results in some functions of photovoltaic glass coatings, they still face the following major challenges:

[0047] Insufficient multifunctionality of coatings: Existing coatings often focus on a single function (such as anti-reflection or self-cleaning) and lack the combination of multiple functions (such as anti-reflection, wear resistance and self-cleaning functions at the same time), which makes traditional coatings limited in improving the comprehensive performance of photovoltaic glass;

[0048] Durability of coatings: Existing coatings, especially self-cleaning coatings and anti-reflective coatings, have poor durability and are easily damaged or fail when exposed to outdoor environments for a long time, affecting the long-term performance of photovoltaic glass;

[0049] Environmental requirements: Traditional coatings use solvent-based coating liquids, which pose a high risk of environmental pollution. Although water-based coatings have appeared, they have not been widely used in the field of photovoltaic glass due to their performance deficiencies (e.g., coating adhesion, wear resistance, UV resistance, etc.);

[0050] The present application discloses a method for preparing a water-based silica core-shell structure coating liquid for photovoltaic glass coating, which aims to improve the anti-reflection performance, wear resistance and self-cleaning function of photovoltaic glass. The implementation steps of the technology include preparation of raw materials, preparation of coating liquid, coating and drying process and optimization of multifunctional coating. The following are the detailed steps and technical parameters for the implementation of the technology;

[0051] 1. Raw material preparation

[0052] Silica: Select silica nanoparticles with a particle size of 30 to 50 nm as the core material of the core-shell structure. Silica has good optical properties and is suitable for use as a substrate for anti-reflective coatings.

[0053] Functional Materials:

[0054] Organosilanes, such as methyltriethoxysilane or MTES, are used to coat the surface of silica particles to enhance the adhesion and water resistance of the coating;

[0055] Fluoride (such as sodium fluoride), as the outer layer of the coating, gives the coating good hydrophobicity and enhances its self-cleaning function;

[0056] Aqueous solvent, using deionized water as solvent, avoids environmental pollution caused by traditional organic solvents and meets the requirements of green manufacturing;

[0057] 2. Preparation of coating solution

[0058] The aqueous silica core-shell structure coating solution is prepared by a sol-gel method, specifically comprising:

[0059] Sol preparation:

[0060] An appropriate amount of silica nanoparticles was added to deionized water and dispersed using an ultrasonic oscillator to obtain silica sol. To ensure uniform dispersion, the oscillation time was controlled at 30 minutes and the power was 500W.

[0061] Adding functional materials:

[0062] Add appropriate amounts of organosilane and sodium fluoride to the silica sol, and stir with a magnetic stirrer for more than 2 hours to make it uniformly mixed. At this time, the organosilane and sodium fluoride will combine with the silica particles to form a core-shell structure;

[0063] Adjust pH:

[0064] According to the formula requirements, adjust the pH value of the solution to 5-6 to ensure that the hydrolysis and polycondensation reactions of the organosilane proceed smoothly;

[0065] To form a stable dispersion:

[0066] Continue stirring for more than 5 hours to ensure that all ingredients react completely to form a stable aqueous dispersion;

[0067] 3. Coating and drying

[0068] Coating method:

[0069] According to the surface morphology of photovoltaic glass, select the appropriate coating method, including dip coating, spray coating or spin coating. For large-area photovoltaic glass, dip coating is recommended. Immerse the cleaned photovoltaic glass substrate in the coating liquid and keep the dipping time for 30 seconds to 1 minute to ensure that the coating is evenly covered on the glass surface. The dipping time can be adjusted according to the specific situation to ensure that the coating is evenly covered on the glass surface.

[0070] Drying treatment:

[0071] The coated photovoltaic glass substrate was placed in an oven for preliminary drying. The oven temperature was set at 60°C and the drying time was 15 minutes to allow the coating to stably adhere to the glass surface.

[0072] To further improve the adhesion and wear resistance of the coating, a medium-temperature annealing treatment was used. The photovoltaic glass substrate was placed on a heating plate with the temperature set at 120°C and the annealing time set at 20 minutes. This process helps to further fix the coating and improve the density and stability of the coating.

[0073] 4. Optimization of multifunctional coatings

[0074] Anti-reflection performance optimization:

[0075] By adjusting the particle size and distribution of silica particles, the refractive index of the coating is controlled to be lower than that of the glass substrate, thereby increasing light transmittance and reducing light reflection. The ideal silica particle size is 30-50nm, and the particle size distribution is uniform, which can effectively reduce surface reflection.

[0076] Optimized wear resistance and self-cleaning performance:

[0077] By adjusting the ratio of organic silane and fluoride in the coating, the wear resistance and self-cleaning performance of the coating can be further improved. A higher ratio of sodium fluoride can enhance the hydrophobicity of the coating, so that the glass surface has a good self-cleaning function. The wear resistance test is carried out using a hardness tester. The coating hardness can reach more than 3H, and the surface friction coefficient is controlled below 0.2;

[0078] The self-cleaning test uses a rain simulation experiment to evaluate the dirt removal effect of the coating under simulated rainfall conditions. The experimental results show that the coating can quickly remove surface dirt after rainfall, showing good self-cleaning effect;

[0079] 5. Performance evaluation and testing

[0080] Light transmittance test:

[0081] The light transmittance of the coated photovoltaic glass was tested using a spectrophotometer to evaluate the anti-reflection performance of the coating. The experiment showed that the coating could increase the light transmittance by 3-5%, effectively reducing light reflection loss;

[0082] Wear resistance test:

[0083] Friction and wear tests on the coating showed that the coating's wear resistance was enhanced, the depth of scratches on the glass surface was reduced by more than 50% compared to uncoated glass, and the service life was extended by 3 to 5 times;

[0084] Self-cleaning performance test:

[0085] Sewage was dripped on the surface of photovoltaic glass to simulate the accumulation of pollutants in the natural environment. The self-cleaning ability of the coating was tested by simulating the rainfall process. The experimental results show that the coating has good self-cleaning function and can quickly remove surface dirt after rainfall to maintain the transparency of the glass surface.

[0086] By implementing the above steps, a water-based silicon dioxide core-shell structure coating liquid photovoltaic glass coating with excellent anti-reflection, wear resistance and self-cleaning functions can be prepared. This technology not only effectively improves the performance and service life of the photovoltaic system, but also meets the green and environmentally friendly manufacturing requirements and has broad market application prospects.

[0087] The technical solution of the present invention is described above in conjunction with specific implementation methods, but it should be noted that the above descriptions are only for explaining the solution of the present invention and cannot be interpreted in any way as a specific limitation on the scope of protection of the invention. Based on the explanation here, those skilled in the art can think of other specific implementation methods or equivalent replacements of the present invention without creative work, and they will all fall within the scope of protection of the present invention.

Claims

1. A method for preparing photovoltaic glass with water-based silicon dioxide core-shell structure coating liquid, characterized in that: The preparation method comprises: S1: Preparation of raw materials Silicon dioxide, as the core material of the core-shell structure, has good optical properties and is suitable as a substrate for anti-reflective coatings; Organosilane, used to coat the surface of silica particles to enhance the adhesion and water resistance of the coating; Fluoride, as the outer layer of the coating, gives the coating good hydrophobicity and enhances its self-cleaning function; Aqueous solvent, using deionized water as the aqueous solvent; S2: Preparation of coating solution: Preparation of water-based silica core-shell coating solution by sol-gel method: Add silica nanoparticles into deionized water and disperse them to obtain silica sol; Add appropriate amounts of organosilane and fluoride to the silica sol, and stir with a magnetic stirrer to mix them evenly. At this time, the organosilane and sodium fluoride will combine with the silica particles to form a core-shell structure; According to the formula requirements, the pH value of the solution is adjusted to 5-6 to ensure that the hydrolysis and polycondensation reactions of the organosilane proceed smoothly; Continue stirring for a certain period of time to ensure that all ingredients react completely to form a stable aqueous dispersion; S3: Coating and Drying Select dip coating, spray coating or spin coating for coating according to the surface morphology of photovoltaic glass; Drying treatment: Place the coated photovoltaic glass substrate in an oven for preliminary drying, set the oven temperature, and control the drying time to ensure that the coating adheres stably to the glass surface; in order to further improve the adhesion and wear resistance of the coating, a medium-temperature annealing treatment is used. Place the photovoltaic glass substrate on a heating plate, set the temperature to 120°C, and anneal for 20 minutes to further fix the coating and improve the density and stability of the coating; S4: Coating Optimization The refractive index of the coating can be controlled by adjusting the particle size and distribution of silica particles, and the wear resistance and self-cleaning properties of the coating can be further improved by adjusting the ratio of organosilane and fluoride in the coating. S5: Performance Evaluation and Testing Including light transmittance test, abrasion resistance test and self-cleaning performance test.

2. The method for preparing photovoltaic glass with an aqueous silicon dioxide core-shell structure coating liquid according to claim 1, characterized in that: The silicon dioxide is silicon dioxide nanoparticles with a particle size of 30 to 50 nm.

3. The method for preparing photovoltaic glass with aqueous silicon dioxide core-shell structure coating liquid according to claim 1, characterized in that: The organosilane is methyltriethoxysilane or MTES, and the fluoride is sodium fluoride.

4. The method for preparing photovoltaic glass with aqueous silicon dioxide core-shell structure coating liquid according to claim 1, characterized in that: In the step S2, after adding the silicon dioxide nanoparticles into deionized water, an ultrasonic oscillator is used to disperse the particles. The oscillation time is 30 to 40 minutes and the power is 500 W to obtain a silicon dioxide sol.

5. The method for preparing photovoltaic glass with aqueous silicon dioxide core-shell structure coating liquid according to claim 1, characterized in that: The hardness of the coating is greater than or equal to 3H, and the surface friction coefficient is less than 0.2.

Citation Information

Cited By

  • Room-temperature cured photovoltaic antireflection coated glass and preparation method thereof

    CN120463430A